Grape seed extract supplement increases bone callus formation and mechanical strength: an animal study - Gurger, Murat; Yilmaz, Erhan; Yilmaz, Seval; Once, Gokhan; Konuk, Mustafa; Kaya, Emre; Artas, Hakan (Bmc, 2019)
BackgroundThe positive effects of grape seed proanthocyanidin extract (GSPE) on bone health, which is a potent antioxidant, are known but its effects on fracture healing are not sufficiently covered in the literature. This study aims to investigate the effects of GSPE on fracture healing and biomechanics of healing bone.Materials and methodsSixty-four adult Wistar-Albino male rats were divided into 8 groups of 8 animals in each group. Osteotomy was performed to the right femurs of all groups except the negative control (G1) and positive control (G2) groups, and intramedullary Kirchner wire was used for fixation. GSPE was given to half of the rats (G2-G4-G6-G8) 100mg/kg/day by oral gavage. The rats were sacrificed on the tenth (G3-G4), twentieth (G5-G6), and thirtieth (G1-G2-G7-G8) days, respectively, and histopathological, radiological, and biomechanical examinations were performed.ResultsHistopathological examination of the specimens from the callus tissues revealed that bone healing was more prominent in the groups supplemented with GSPE (G4, G6, G8). There was a statistically significant improvement in radiological recovery scores and callus volumes in groups with GSPE. When biomechanical strengths were evaluated, it was found that GSPE increased bone strength not only in fracture groups but also in the positive control group (G2).ConclusionsAs a result, this study showed that GSPE, a potent anti-oxidant, had a positive effect on bone healing and improved mechanical strength of the healing bone.
Keywords: Grape seed; Proanthocyanidin; Antioxidant; Fracture healing; Biomechanics